Luke's gold - West, Charles (Berkley, 2022)
"Ever since he was fourteen, Cade Hunter has made his way through his own sweat and blood, with no place to call home. Most think he's not much more than a drifter. But veteran ranch hand Luke Tucker sees a resourceful youngster who's as honest as he is tough, which is why Luke shares a secret with Cade--a secret worth its weight in Union gold. When Luke and Cade make a move to find the lost fortune, Luke's past returns in the form of Lem Snider--a vile, thieving cur who murders Luke and leaves Cade for dead. But Cade isn't dead. And he's not planning on dying. Because now he has something to live for: revenge"--Page 4 of cover.